2001
DOI: 10.1007/s004170100287
|View full text |Cite
|
Sign up to set email alerts
|

Transforming and insulin-like growth factors in the aqueous humour of patients with exfoliation syndrome

Abstract: Since TGF-beta1 induces the synthesis and accumulation of extracellular matrix, it is hypothesized that TGF-beta1 plays an important role in the pathogenesis of XFS. Our data suggest that the increased levels of TGF-beta1 are most likely due to enhanced local synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
13

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 47 publications
3
34
0
13
Order By: Relevance
“…It is well known that growth factors and proteases can be activated by free radicals, so the occurrence of oxidative stress and therefore the antioxidant status of the aqueous humour may play a role in the oxidative metabolism of the cells implicated in the production of exfoliative material. [6][7][8] Oxidative stress can be defined as an increase in the intracellular concentrations of reactive oxygen species (ROS) over physiological values. 9 This situation may be reflected by changes in the antioxidant defences that can be depleted because of the ROS action or increased as a protective response.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that growth factors and proteases can be activated by free radicals, so the occurrence of oxidative stress and therefore the antioxidant status of the aqueous humour may play a role in the oxidative metabolism of the cells implicated in the production of exfoliative material. [6][7][8] Oxidative stress can be defined as an increase in the intracellular concentrations of reactive oxygen species (ROS) over physiological values. 9 This situation may be reflected by changes in the antioxidant defences that can be depleted because of the ROS action or increased as a protective response.…”
Section: Introductionmentioning
confidence: 99%
“…In the surrounding media, the human anterior chamber fluid, there is a lack of epidermal growth factor and TGF-· [11] as well as the presence of other growth factors such as bFGF, TGF-ß and vascular endothelial growth factor [12,13]. Most interestingly, the presence of TGF-ß 1 in anterior chamber fluid was recently reported [14]. We report herewith our investigation into the presence of CTGF in human anterior chamber fluid.…”
Section: Introductionmentioning
confidence: 83%
“…One of these growth factors, TGF-ß 1 , which is known to lack a suppressive effect on inflammation by T-cell induction [19], has been detected in anterior chamber fluid [20]. Elevated levels of TGF-ß 1 have only recently been reported to occur in eyes with exfoliation syndrome [14,20].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic associations found in XFS include angina pectoris, hypertension, myocardial infarction, and stroke. An active involvement of the trabecular meshwork in this abnormal matrix process that leads to a progressive accumulation of XFS material in the juxtacanalicular tissue is considered as the possible cause of chronic high pressure in XFS eyes (Schöltzer-Schrehardt et al, 1992;Koliakos et al, 2001). The principal ocular cells implicated in the production XFS material are those closely associated with the aqueous humor circulation and are influenced by the substances that are present in it.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of qualitative and quantitative alterations of the aqueous humor composition might, therefore, provide an important insight into the factors involved in this disorder. Recent studies reported differences in the concentration of matrix metalloproteinases (Schöltzer-Schrehardt et al, 2003) and growth factors (Koliakos et al, 2000(Koliakos et al, , 2001 in the aqueous humor of XFS patients. It is well known that growth factors and proteases can be activated by free radicals, so the occurrence of oxidative stress and therefore the antioxidant status of the aqueous humor may play a role in the oxidative metabolism of the cells implicated in the production of exfoliative material.…”
Section: Introductionmentioning
confidence: 99%